Суб’єктний складник аграрного питання як одна з передумов Української революції 1917–1921 рр. - Корновенко, С.В. (Український історичний журнал, 2017)
Розглядається суб’єктний фактор аграрного питання як одна з передумов
Української революції 1917–1921 рр. Обґрунтовано причини глибинних соціокультурних трансформацій на селі початку ХХ ст. На авансцені історії з’явився
новий активний суб’єкт – селянин-ідеоман. Селянська революційність стала
каталізатором інституційних змін тогочасної російської імперської моделі.
В Українську революцію 1917–1921 рр. селянство ввійшло зі значним досвідом
поведінки активного суб’єкта історії, багато у чому зумовивши її причини, перебіг і фінал. The author in this article examines the subject factor of the agrarian question as one
of the preconditions of Ukrainian revolution of 1917–1921. In this article substantiated
the reasons of the deep sociocultural transformations in the villages in the early
20th century. On the forefront of history appeared the new active subject – the peasantideоman.
Peasant revolutionism became some kind of the catalyst for institutional
changes of thenadays Russian imperial model. The peasantry came into the Ukrainian
Revolution of 1917–1921 with considerable experience of the behaviour as the active
subject of history, largely predetermining its causes, course and finale.